2009
DOI: 10.1098/rsbl.2009.0150
|View full text |Cite
|
Sign up to set email alerts
|

Foraging segregation between two closely related shearwaters breeding in sympatry

Abstract: Trophic segregation has been proposed as a major mechanism explaining the coexistence of closely related animal taxa. However, how such segregation varies throughout the annual cycle is poorly understood. Here, we examined the feeding ecology of the two subspecies of Cory's shearwater, Calonectris diomedea diomedea and Calonectris diomedea borealis , breeding in sympatry in a Mediterranean colony. To study trophic segregation at different stages, we combined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 17 publications
5
59
0
Order By: Relevance
“…Indeed, our study was conducted during the pre-laying period whereas that of Forero et al (2006) occurred during incubation (males, of course, do not lay eggs), and haematocrit increases between pre-laying and chick-rearing in female Cory's shearwaters, whereas it remains stable in males . Given that (1) the Cory's shearwaters from the Azores and those studied by Forero et al (2006) and forage in different areas Magalhães et al 2008;Navarro et al 2009), and (2) the haematocrit values we found were higher than those obtained by during the same period of the breeding cycle, the role of geographical origin (i.e. whether environmental conditions might be more stressful at one locality) cannot be dismissed either (Edwards et al 2006).…”
Section: Discussionmentioning
confidence: 66%
“…Indeed, our study was conducted during the pre-laying period whereas that of Forero et al (2006) occurred during incubation (males, of course, do not lay eggs), and haematocrit increases between pre-laying and chick-rearing in female Cory's shearwaters, whereas it remains stable in males . Given that (1) the Cory's shearwaters from the Azores and those studied by Forero et al (2006) and forage in different areas Magalhães et al 2008;Navarro et al 2009), and (2) the haematocrit values we found were higher than those obtained by during the same period of the breeding cycle, the role of geographical origin (i.e. whether environmental conditions might be more stressful at one locality) cannot be dismissed either (Edwards et al 2006).…”
Section: Discussionmentioning
confidence: 66%
“…Seabird species often breed in large communities and target productive areas within their foraging range, leading to intense competition for resources [1] and reduced foraging efficiency [2]. Seabirds can avoid interspecific competition at least partially by ecological segregation in foraging areas [3,4], diving depths [4,5] or diet choice [6,7]. However, little is known from pelagic birds during the non-breeding season, when seabirds forage over much larger spatial scales.…”
Section: Introductionmentioning
confidence: 99%
“…First, nestling CORT should be related to variation in duration of foraging trips and foraging efficiency (FE) of parents (i.e. rate of mass gained at sea; see below) because these are measures of parental effort that vary with increasing costs to parents [7,34]. In our population, foraging costs increase with increasing trip length [7] and, at least in other populations, longer trips result in less food being delivered per day to shearwater chicks [35].…”
Section: Introductionmentioning
confidence: 99%